Dietary astaxanthin improves the antioxidant capacity, immunity and disease resistance of coral trout (Plectropomus leopardus). Issue 122 (March 2022) - Zhu, Xiaowen; Hao, Ruijuan; Zhang, Junpeng; Tian, Changxu; Hong, Yucong; Zhu, Chunhua; Li, Guangli
Abstract: The effects of astaxanthin on growth performance, digestive enzyme activity, antioxidant capacity, immune ability, resistance to Vibrio harveyi infection of coral trout ( Plectropomus leopardus, initial weight 17.44 ± 0.05 g) were studied by 8-week feeding trial. Four iso-nitrogenous and iso-lipidic experimental diets containing astaxanthin 0 (A0), 0.05 (A1), 0.1 (A2) and 0.2 (A3) g/kg were formulated with the addition of Haematococcus pluvialis powder (astaxanthin content accounts for 100 g/kg) of 0, 0.5, 1.0 and 2.0 g/kg, separately. The feeding experiment lasted for 56 days, and it was found that supplementing the diet with astaxanthin-rich H. pluvialis powder had no significant impact on the growth performance about coral trout ( P > 0.05). Compared with the A0 group, the activities of amylase, lipase, and trypsin in the liver of the A2 group was dramatically increased ( P < 0.05); catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px) activities and total antioxidant capacity (T-AOC) level in serum and liver were dramatically higher in the A2 group before as well as after the challenge ( P < 0.05); after the challenge, the acid phosphatase (ACP) and lysozyme (LZ) activities, and complement (C3 and C4) contents in serum and liver were significantly raised for the A2 group ( P < 0.05); the liver relative expressions of copper-zinc superoxide dismutase ( sod-1 ), manganese superoxide dismutase ( sod-2 ), cat, acp6, akp, lz-c, immunoglobulin M ( igm ), c3, and c4-b in the A2 group were significantly up-regulated before and after the challenge ( P < 0.05); the rate of survival follow V. harveyi challenge in the group A2 was dramatically higher ( P < 0.05). In summary, this study indicated that adding 1.0 g/kg astaxanthin-rich H. pluvialis powder (the content of astaxanthin is 0.091 g/kg) could improve the digestive enzyme activity, antioxidant capacity, immunity, and the ability to resist the challenge of V. harveyi in coral trout. Highlights: Adding 0.091 g/kg astaxanthin improves digestive enzyme activity of coral trout. Astaxanthin level of 0.091 g/kg improves the antioxidant capacity of coral trout. With 0.091 g/kg astaxanthin, immunity and disease resistance can be improved.